Existence of positive solutions for a class of p-Laplacian fractional differential equations with nonlocal boundary conditions - Jiqiang Jiang; Xuelin Sun (Boundary Value Problems, 2024)
Abstract This article is devoted to proving the uniqueness of positive solutions for p-Laplacian equations with Caputo and Riemann-Liouville fractional derivative. The uniqueness result and the dependence of the solution on a parameter are established based on the fixed point point theorem of mixed monotone operators. In the end, a numerical simulation is given to verify the main results.